Interaction between antibiotic use and MS4A2 gene polymorphism on childhood eczema: a prospective birth cohort study - Li Hua; Qian Chen; Quan-Hua Liu; Yi-Feng Guo; Ru-Hong Cheng; Jun Zhang; Jian-Hua Zhang; Li-Wei Wang; Ruo-Xu Ji (BMC, 2021)
Abstract Background Eczema is usually the first allergic manifestation to appear in life attributed to gene-environment interactions. IL13, IL4, MS4A2 and ILR4A are four key inflammatory genes associated with atopy. This study aimed to explore gene-environment interactions on eczema in early life among the above four genes and environmental factors in Chinese Han children. Methods Five hundred ninety-seven children from a birth cohort who completed two-year follow-up were enrolled and their cord blood was collected. Subjects were genotyped for six polymorphisms in the aforementioned four genes. The children were followed at 6, 12 and 24 months, with epidemiologic information and medical history of eczema collected by questionnaire and eczema assessed by dermatologists. Results Among the 597 children, 168 were diagnosed with eczema and the others were not after 2 years of follow-up. MS4A2 rs569108 GG genotype (P = 1.68E-02, odds ratio (OR) = 4.66) and antibiotic use (P = 3.75E-4, OR = 2.02) were found independently associated with development of childhood eczema. Children with both antibiotic use and MS4A2 rs569108 GG genotype were more likely to develop eczema than those with only antibiotic use or GG homozygote (OR = 6.24 VS. 2.04 or 4.68). Conclusions MS4A2 rs569108 polymorphism and antibiotic use were solely associated with eczema, and they interacted with each other to increase the risk of developing the disease in Chinese Han toddlers. Long-term follow-up along with functional and replication studies are still needed.